(untitled) (SCHOOLAR: Social and Literature Study in Education, 2024)
The researcher’s concern about the decline in Quran reading among students in Junior High School has led to the application of the drill method through the Islamic Religious Local Content lesson, hoping to enhance Quran reading in schools and be applicable in the community and beyond. Therefore, this study aims to examine, analyze, and describe the Implementation of the Drill Method for Quran Reading in the Islamic Religious Local Content subject. This research is a quantitative study conducted at SMPN 1 Megaluh, located in Dusun Paritan, Sudimoro Village, Megaluh Subdistrict, Jombang Regency, East Java Province. The researcher implemented the study in class IX A, which used the drill method (experimental class) with 28 students, and class IX B (control class) with 28 students. The results indicate that the Implementation of the Drill Method is more effective in improving Quran reading learning outcomes compared to using the Tartil method. Most students at SMPN 1 Megaluh come from rural areas and are more suited to learning methods that involve repetition, such as the drill method. As evidence, after the research, the average score of students in class IX A using the drill method was 91.25, while class IX B using the tartil method had an average score of 75.7.